RESPON WALI MURID TERHADAP PERAN MUHAMMADIYAH DALAM MENGEMBANGKAN PENDIDIKAN (Studi Kasus SD Muhaammadiahah 3 Kelurahan Tangkerang Barat, Kecamantan Marpoyan Damai Kota Pekanbaru) - Asmaul Husna; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Muhammadiyah organization is an Islamic movement, missionary movement amar makhruf nahi mungkar, who berakidah Islam and sourced from the Qur'an and sunnah maqbullah (accepted) therefore Muhammadiyah is persarikatan that moves Muslims to fight and jihad on the way of Allah. Muhammadiyah also instilled an important role in the field education. It is proven by the rampant development of Muhammadiyah educational institution in Marpoyan Damai sub-district, Pekanbaru city. Based on pre-survey conducted by the researcher, it can be seen as phenomenon such as, Parents strongly support the regulations that have been set in SD Muhammadiyah 3 Pekanbaru. and there are some guardians who disagree on the extracurricular activities of Muhammadiyah for 5th and 6th grade students for fear of interrupting the teaching and learning process during class hours considering they will take the national exam. Theories used are response theory, role theory and motivation theory. Data analysis was done by quantitative descriptive analysis, the data collecting technique in this research is purposive sampling where the respondent is 43 people consisting of guardian of class V and VI students. From the results of field research diketahuibah motivation parents to send their children in elementary school Muhammadiyah 3 seen from the dimensions of social status, facilities, and infrastructure, religious values and achievements, the greatest of motivation is the value of religion, parents' response indicates that parents interested in schools Muhammadiyah , this is in line with the assumption of parents to the role of muhammadiyah in developing education.Keywords: Response, Student Guardian, Role, Education SD Muhammadiyah 3